Phonetic and Spelling Peculiarities of Advertising Discourse in Modern Armenian - SARGSYAN, LIANA (Bulletin of Yerevan University B: Philology, 2021)
This article discusses some phonetic peculiarities of modern advertising discourse. Particular attention is paid to such phonetic manifestations that affect the viewer, listener, reader, attract their attention and contribute to the perception and memorization of the text being advertised. On the example of various texts of RA advertising discourse, different manifestations of euphony of speech, the right combinations of sounds, rhyme, rhythm, and stress are scrutinized, and their importance is emphasized. There is another peculiarity in the Armenian advertising texts: there are two types of contamination that are typical of modern Armenian advertising text, as well as the names of different products, banks, shops, etc. that are written in Latin letters. The article provides detailed explanations of linguistic and extralinguistic reasons for such manifestations, the objectives, the productivity of turning to non-standard forms, deviation from the norms of the literary language are presented.